2018
DOI: 10.1016/j.energy.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

A spatial electricity market model for the power system: The Kazakhstan case study

Abstract: wkpl essemyev a,b D tons igerer b,e D omn wendelevith c,d, * D xurkht hkiyev a a xzryev niversityD xtionl vortory estnD vortory inergyD iology nd glimteD SQ uny tyr veFD HIHHHH estn b ehnishe niversit¤ t ferlinD orkgroup for snfrstruture oliy @sAD trße des IUF tuni IQSD IHTPQ ferlin c qermn snstitute for ionomi eserh @hs ferlinAD heptF inergyD rnsportD invironmentD wohrenstrF SVD IHIIU ferlin d rumoldt niversi¤ t zu ferlinD esoure ionomis qroupD nter den vinden TD IHWWW ferlin e priedrihEelexnderEniversit¤ t i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Table 2 provides an overview of the data in an aggregated fashion.
Fig. 2Conventional and renewable power plants capacity in Kazakhstan in 2015.Source: Own figure based on [1].
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 provides an overview of the data in an aggregated fashion.
Fig. 2Conventional and renewable power plants capacity in Kazakhstan in 2015.Source: Own figure based on [1].
…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…This article explains the input data (excel file) which was used for a detailed analysis of the electricity system of [1] and to provide additional information on data acquisition and compilation. A combination of quantitative and qualitative approaches was used in the data analysis of network topology and characteristics, demand variation and distribution, technical and economic parameters for conventional and renewable generation, as well as availability time series, and imports and exports.…”
Section: Datamentioning
confidence: 99%
“…Based on previous research, this paper tries to explore Kazakhstan's CO 2 emissions in the post-Kyoto Protocol era, which refers to both production-and consumption-based analysis. Assembayeva et al (2018) focused on Kazakhstan's electricity system and used a techno-economic model to account for related particularities; Tokbolat et al (2018) evaluated the efficiency of energy consumption of residential buildings in Astana and Kerimray, as well as the decarbonisation of the residential sector (Kerimray, 2018;Kerimray et al, 2018b); Onyusheva et al (2017) researched a similar topic in the transport and energy sectors. For empirical studies, Li et al (2018) adopted the Logarithmic Mean Divisia Index (LMDI) decomposition and the Stochastic Impacts by Regression on Population, Affluence, and Technology (STIRPAT) model to study major driving factors of CO 2 emissions in Kazakhstan from 1992 to 2013 and Kerimray et al (2018c) used LMDI to analyse energy intensity; Xiong et al (2015) explored the development of Kazakhstan's low-carbon economy by decoupling relationship analysis, reflecting the relationship between energy consumption and economic growth.…”
Section: Introductionmentioning
confidence: 99%
“… Ahmad et al (2017) discussed the potential of the nuclear industry for electricity generation in long-term perspectives. Assembayeva et al (2018) indicated the economic model of the power generation sector in Kazakhstan. According to Karatayev et al (2016) , in case of Kazakhstan, there are three ES definitions provided in a number of documents including National Development Strategy “Kazakhstan 2030” (Directive № 377 of November 05, 1997), Nuclear Development Programme (Directive № 728 of June 29, 2011) and Concept of Developing the Fossil Fuel and Power Generation complex up to 2030 (Directive № 724 of June 28, 2014).…”
Section: Energy Security Conceptualisationmentioning
confidence: 99%